Solarization of electric tube-wells for agriculture in Balochistan: Economic and environmental viability - Rana, Abdul Wajid; Davies, Stephen; Moeen, Muhammad Saad; Shikoh, Sania Haider; Rizwan, Noormah (International Food Policy Research Institute, 2020)
Balochistan’s agriculture and related economic development during the last four decades has been driven by an enhancement in canal command areas and widespread use of tubewells. While it enabled yield increases and the growth of high value horticulture, it led to excessive mining of ground water. It is not only threatening sustainable agriculture and livelihoods but also creating severe environmental repercussions. It is generally believed that this unchecked groundwater extraction has been a result of policy regime, such as promoting installation of tubewells through various incentive schemes and tubewells subsidy which allows farmers to pay only 5-10% of the actual cost, and as a result the Federal and provincial governments have been paying PKR 23 billion per year.